Field tests of the mobile lidar for tropospheric ozone sensing on horizontal (inclined) and vertical paths - Nevzorov Alexey; Tuzhilkin Dmitry; Nevzorov Aleksey (E3S Web of Conferences)
The results of field tests of the mobile lidar for ozone sensing on horizontal (inclined) and vertical paths are presented. The lidar operates on the basis of the differential absorption and scattering method at wavelengths of 299/341 nm and allows receiving lidar signals on a trace up to ~18 km long. The lidar was installed on an isothermal van with an autonomous power supply system. Field tests were conducted on the territory of Tomsk. An example of field measurements is given and the result of lidar sensing is presented.